The Phenomenon of Self-Diagnosis Behavior on Self-Healing Style in Young People - Ginting, Eraskaita; Hati, Putri Citra (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2023)
The phenomenon of self-diagnosis, which is widely discussed on social media, has made many young people carry out self-healing in their way. This research aims to discover how self-diagnosis behavior affects the style of self-healing in young people and whether the concept of self-healing, which is popular among the younger generation, is by actual self-healing. This research method uses a qualitative descriptive approach with literature studies and data collection through secondary data obtained through literature studies such as reference books, journals, articles, and other sources related to research. The results of this research show that stigma and discrimination are still obstacles for mental health sufferers in getting appropriate and adequate treatment. This triggers the younger generation to carry out self-healing independently in their style, and this has an impact on the actual concept of healing. Several ways can be used as references for young people for self-healing, including mindfulness, guided imagery, self-talk, and expressive writing.